Hypertension treatment features in perimenopausal women - Yu V Zhernakova; I E Chazova (Системные гипертензии, 2014)
Major causes of disability among women are chronic heart failure, developed on arterial hypertension (AH) and cerebral stroke. However, the prevalence of AH among postmenopausal women is significantly higher than for men. Women are more likely to develop AH with metabolic disorders, including metabolic syndrome. Therefore, the drugs of choice to treat AH in women in perimenopauseare ACE inhibitors and Angiotensin II Receptor Blocker. If necessary, combination antihypertensive treatment drugs of choice are agonistsimidazoline receptors, such as moxonidine. The use of this category of patients havemoxonidine action justified by the features of the pharmacological action of this drug (decrease in sympathetic hyperactivity), high efficiency, antihypertensive as well as additional positive effects on body weight and metabolic parameters.